Governance Models in Education: Insights for Nepal’s Federal Education System - Bhatta, Narayan Prasad (AMC Journal, 2024)
This article explores educational governance by reviewing relevant literature, policies, and reports from different contexts and countries. Employing a desk review method, it investigates various governance frameworks, including centralized, decentralized, and hybrid models, to evaluate their impacts on education systems. The results indicate that decentralized governance generally enhances school autonomy and accountability, fostering innovation and local responsiveness. In contrast, centralized systems tend to be more effective in upholding uniform standards and consistent service provision. Hybrid models present a balanced solution by blending the benefits of both governance approaches. Drawing lessons from global experiences, the article delivers insights for developing an effective governance framework for Nepal's evolving federal education system. It emphasizes the importance of a governance model that promotes equitable access to quality education while allocating the responsibilities among the three tiers of government.